1993
DOI: 10.1002/cber.19931261202
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Struktur des ersten oligomeren cyclischen Dimethylsilyl‐substituierten Carbodiimids

Abstract: New oligomeric cyclic silylcarbodiimides 1-3 are synthesised by the reaction of the respective dichlorosilanes with cyanarnide. From the resulting reaction mixture with dichlorodimethylsilane the tetrameric compound of the hypothetical [(CH3)2Si=N-CN] is isolated. In this molecule sixteen atoms build a nearly planar ring structure with a special steric arrangement of the groups. This oligomeric silylcarbodiimides present a new kind of precursors for the pyrolytic synthesis of ceramics in the ternary system SiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…1, the molecular structure and the side groups that are connected to silicon vary depending on the organosilane initially used. According to these routes, precursors like polymethylvinylsilazane (PMVS), 6,25 polyhydridomethylsilazane (PHMS) 26 as well as the corresponding polysilylcarbodiimides PMVC 18 and PHMC 21 have been synthesized. Besides Si-C-N precursors, preceramic compounds for Si-B-C-N ceramics have gained significance because of the outstanding thermal stability of the resulting quaternary ceramics.…”
Section: Polymer Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, the molecular structure and the side groups that are connected to silicon vary depending on the organosilane initially used. According to these routes, precursors like polymethylvinylsilazane (PMVS), 6,25 polyhydridomethylsilazane (PHMS) 26 as well as the corresponding polysilylcarbodiimides PMVC 18 and PHMC 21 have been synthesized. Besides Si-C-N precursors, preceramic compounds for Si-B-C-N ceramics have gained significance because of the outstanding thermal stability of the resulting quaternary ceramics.…”
Section: Polymer Systemsmentioning
confidence: 99%
“…The second unit constituting the backbone is -NH-groups in the case of polysilazanes [5][6][7]9,[14][15][16][17] and carbodiimiide groups in the case of polysilylcarbodiimides. [18][19][20][21][22] These polymers are obtained by the condensation reaction of organochlorosilanes with ammonia and cyanamide respectively. In contrast to reactions involving the formation of the solid byproducts ammonium chloride and pyridinium hydrochloride pyÁHCl, polysilylcarbodiimides can also be obtained via the reaction of organochlorosilanes with bis(trimethylsilyl)carbodiimide, yielding trimethylchlorosilane as a by-product, which can be easily removed by distillation.…”
Section: Polymer Systemsmentioning
confidence: 99%
“…The 29 Si-NMR spectrum indicates a linear structure of the PV polymer, as also reported in the literature [6,15]. The 29 Si-NMR spectrum of MHMV displays 4 main signals at −61 ppm for [8] and 1 ppm corresponding to Si(CH 3 ) 3 endgroups (see Fig. 1).…”
Section: Materials Characterizationmentioning
confidence: 60%
“…It was shown that polysilylcarbodiimide-derived SiCN materials exhibit higher resistance against crystallization as compared to their polysilazanes-derived analogues [6]. Moreover, polysilylcarbodiimides-based materials can also be synthesized by a non-oxide sol-gel process [7] producing linear, branched or crystalline polymers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…30 The polysilylcarbodi-imides can be transformed in one step to amorphous and singlephase Si-C-N ceramics in a high yield without prior cross-linking. In contrast to the polysilazanes composed of alternating Si-N units, the polysilylcarbodi-imides contain alternating Si-N=C=N units.…”
Section: Materials In the Ternary System Si±c±nmentioning
confidence: 99%